2017
DOI: 10.1021/acs.langmuir.7b02934
|View full text |Cite
|
Sign up to set email alerts
|

Core/Shell Gene Carriers with Different Lengths of PLGA Chains to Transfect Endothelial Cells

Abstract: In order to improve the transfection efficiency and reduce the cytotoxicity of gene carriers, many strategies have been used to develop novel gene carriers. In this study, five complex micelles (MSP(2 k), MSP(4 k), MSP(6 k), MSP(8 k), and MSP(10 k)) were prepared from methoxy-poly(ethylene glycol)-b-poly(d,l-lactide-co-glycolide) (mPEG-b-PLGA) and sorbitol-poly(d,l-lactide-co-glycolide)-graft-PEI (sorbitol-PLGA-g-PEI, where the designed molecular weights of PLGA chains were 2 kDa, 4 kDa, 6 kDa, 8 kDa, and 10 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…The representative structures and 1 H NMR spectra of mP, PP, and PC copolymers were shown in Figure S1. The results demonstrated that these amphiphilic polymers were successfully synthesized …”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…The representative structures and 1 H NMR spectra of mP, PP, and PC copolymers were shown in Figure S1. The results demonstrated that these amphiphilic polymers were successfully synthesized …”
Section: Resultsmentioning
confidence: 89%
“…N‐Hydroxy succinimide (NHS), 1‐ethyl‐3‐(3‐(dimethylamino)propyl)‐carbodiimide hydrochloride (EDC), succinic anhydride, diallylcarbamyl chloride, and 2,2‐dimethoxy‐2‐phenylacetophenone (DMPA) were obtained from Tianjin Heowns Biochemical Technology Co., Ltd. CAGW (Cys‐Ala‐Gly‐Trp) and TAT‐NLS (Gly‐Arg‐Lys‐Lys‐Arg‐Arg‐Gln‐Arg‐Arg‐Arg‐Pro‐Lys‐Lys‐Lys‐Arg‐Lys‐Val) peptides were purchased from GL Biochem (Shanghai) Ltd. EA.hy926 cells (human umbilical vein endothelial cells) were purchased from the American Type Culture Collection (ATCC; Manassas, VA, USA), and cultured as described before . Other chemicals and biological reagents were supplied by the companies referred in our previous study …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations